Sm-Nd garnet ages of retrograde garnet bearing granulites from Tonagh Island in the Napier Complex, East Antarctica: A preliminary study - Owada, Masaaki; Osanai, Yasuhito; Tsunogae, Toshiaki; Hamamoto, Takuji; Kagami, Hiroo; Toyoshima, Tsuyoshi; Hokada, Tomokazu (National Institute of Polar Research, 2001)
P(論文) Proterozoic Sm-Nd garnet ages were dated from a garnet-bearing quartzo-feldspathic gneiss (Grt-felsic gneiss) and an iron rich garnet-pyroxene gneiss (Fe-rich Grt-Py gneiss) in the northern part of Tonagh Island, the Napier Complex. The Grtfelsic gneiss occurs as a member of layered gneiss. The Fe-rich Grt-Py gneiss appears as a block in the felsic gneiss. Since the layered gneiss contains a critical mineral assemblage of ultrahigh-temperature (UHT) metamorphism such as sapphirine+quartz, the Grt-felsic and the Fe-rich Grt-Py gneisses have undergone UHT metamorphism whose age is believed to be Late Archaean. The inclination line connecting with garnet and whole rock in the Grt-felsic gneiss yields an age of 1897 Ma in the Sm-Nd system. The internal isochron using garnet, pyroxenes and whole rock for the Fe-rich Grt-Py gneiss gives an age of 1557±35 Ma. Both Sm-Nd internal isochron ages correspond to Early Proterozoic. Garnet-quartz symplectite and quartz occur between orthopyroxene and plagioclase in the Grt-felsic gneiss. This texture indicates the following reaction: orthopyroxene+plagioclase=garnet+quartz. The garnet in the Fe-rich Grt-Py gneiss occurs as interstitial mineral with small grained clinopyroxene and quartz. Taking reaction textures into account, the garnet forming reactions in the Grt-felsic and the Fe-rich Grt-Py gneisses would occur during retrograde events after UHT peak metamorphism. The ages of c. 1900 and c. 1550 Ma would therefore reflect tectonothermal events in the Napier Complex. departmental bulletin paper